Defecto Septal Ventricular - Peralta, Aurelio (1956)
For a while, following the original description of Roger, the ventricular septal defect was estimated as a benign lesion that does not alter the longevity of the carrier. However, there have been reports of infants and children with severe symptoms and disability states. Edwards, on the basis of anatomical and pathological collection of the Mayo Clinic, established that 19 of 30 patients with isolated ventricular septal defect had died before the age of 6 months. In the series of Maude Abbott, 1,000 autopsies of congenital heart disease, 21 of 50 cases of ventricular septal defects in membranous portion had died before 5 years of age.